Pengaruh Lingkungan Kerja dan Kompensasi Terhadap Kinerja Karyawan di PT Bando Indonesia - Shakila, Firosa; Hastasari, Ratih; Saputra, Wawan (CV Warnak Johanna Nusantara, 2025)
This study examines the variables of work environment and compensation as independent variables, and employee performance as the dependent variable. The purpose of this research is to determine the influence of the work environment and compensation on employee performance at PT. Bando Indonesia, both partially and simultaneously. This research uses a quantitative method. The sample consisted of 90 respondents selected using a non-probability sampling method with purposive sampling technique. Data collection was carried out through the distribution of questionnaires. The data analysis design includes validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. Based on the results of the study, it was found that the work environment variable has a significant partial influence of 0.354 with a significance value of 0.000 on employee performance. The compensation variable also has a significant partial influence of 0.410 with a significance value of 0.000 on employee performance. Simultaneously, the work environment and compensation together have a positive and significant influence on employee performance with a significance value of 0.000 and an F value of 98.066.